Utilization of Treated Wastewater in Construction Activities for Sustainable Development Goal (SDGs) in Johor - Magentharan, Ganeswaran; SABTU, HILYATI; Mohd Nor, Norasmiha; Sallehuddin, Aina Mardia; Sarpin, Norliana; Khalid, Zailawati (Research in Management of Technology and Business, 2026)
This study investigates the utilization of treated wastewater in construction activities within Johor, Malaysia, as a strategic response to escalating freshwater demand and in alignment with Sustainable Development Goals (SDGs) 6 and 11. The construction industry’s heavy reliance on potable water for processes like concrete mixing and dust suppression creates significant sustainability pressures, particularly in rapidly urbanizing regions facing water stress. The research aimed to identify specific non-potable applications for treated effluent, systematically examine the barriers to adoption faced by industry contractors, and propose actionable strategies for integration. A quantitative methodological approach was implemented, utilizing a structured questionnaire disseminated electronically to a targeted sample of 233 contractors registered with the Construction Industry Development Board (CIDB) under Grades G6 and G7, ensuring insights from key decision-makers in medium to large-scale projects. The results identified landscape irrigation, dust suppression, and equipment washing as the most promising applications, with high respondent agreement. However, critical challenges were also highlighted, primarily concerning the inconsistent quality and reliability of treated wastewater supply, high initial economic costs, ambiguous regulatory frameworks, and a prevalent lack of technical awareness among contractors. In conclusion, the study confirms the substantial potential of treated wastewater to enhance sustainable water management in Johor’s construction sector. Realizing this potential requires a concerted effort to address the identified barriers through the development of clear standards, targeted financial or policy incentives, and comprehensive industry education programs.